The associative forms in Romania following the new Civil Code, republished in 2011 - Angela MIFF (Juridical Tribune, 2013)
During time, the association has evolved as a form of socio-economic organisation in order to perform non-professional or, by case, professional activities. The legislative sources have emphasized, in time, the variety of the ways of manifestation of the association among different law subjects – physical and/or legal persons. The new Civil Code (2009), republished in 2011, in force since the 1st October 2011, fundamented on the monist approach of regulation, as the common-law norm for all the domains that the letter and the spirit of its provisions refer to, regulates the contract of association, in chapter VII of the 5thBook; apart from the general norms applicable to all such contracts of association, the present code replaces the former civil society without legal personality with the present simple society and, also as a novelty element, transposes the regulation of the silent partnership from the former framework of the Commercial Code (1887, abrogated almost in totality) in the section 3 of the same chapter VII, the 5th Book of the code. The elements that are similar with the former regulation outline the continuity aspects in the conception of these juridical institutions in a modern approach that transposes aspects which were clarified by the jurisprudence or the legal doctrine.